Pengaruh Efisiensi Waktu Tunggu dan Kenyamanan terhadap Kepuasan Pasien di Puskesmas Bantarbolang - Sinta Wulandari; Yuniarti Yuniarti; Teguh Irawan (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
The quality of health services at community health centers can be indicated by patient satisfaction. Patient satisfaction shows how good the health service is. Patient satisfaction is measured by comparing the experience with the patient's expectations. Patient dissatisfaction can be caused by the behavior of medical personnel, as well as system factors such as waiting time and facility comfort. This study aims to determine the effect of waiting time and comfort on patient satisfaction at the Bantarbolang Community Health Center. Using a quantitative method, a cross sectional approach with a sample size of 98 patients, the sampling technique was incidental sampling. The majority of respondents were female (76.5%), aged <20 to 30 years (54.1%), and had a high school/vocational school educational background (41.8%). Most patients experience waiting times that exceed the standards set by Minister of Health Regulation No. 30 of 2022 (75.5%), the average waiting time is the longest in dental clinics (120 minutes). The majority of patients had a low level of comfort (60.2%). Although the majority were satisfied with the service (73.5%), the analysis showed a significant influence between waiting time and patient satisfaction (p-value=0.003). However, there was no significant influence between comfort level and patient satisfaction (p-value=0.703).